Riverine regime shifts through reservoir dams reveal options for ecological management. Issue 7 (27th August 2018) - Meißner, T.; Schütt, M.; Sures, B.; Feld, C. K.
Abstract: Worldwide, dams are a main threat reducing river ecological functioning and biodiversity by severely altering water temperature, flow, and sediment regimes up‐ and downstream. Sustainable dam management therefore has a key role in achieving ecological targets. Here, we present an analysis of the effects of reservoir dams and resulting regime shifts on community structure and function of lotic macroinvertebrates. Our study derived management options to improve ecological integrity of affected streams. To do this, we contrasted time series data for water temperature (15‐min intervals over one year), discharge (daily means over 10 yr), and records of deposited fine sediments against macroinvertebrate samples from pairs of river reaches downstream of dams and of comparable tributaries not affected by dams in the German low mountain range. We observed a decline in the density and diversity of disturbance‐sensitive macroinvertebrates (Ephemeroptera, Plecoptera, and Trichoptera) and a correlation between hydrologic metrics and macroinvertebrate deterioration downstream of the dams. Typical "rhithral" (flow‐adapted) species changed to "littoral" (flow‐avoiding) species below dams, thus indicating a hydrologic regime shift. Increased fine sediment accumulations and deficits of pebbles and small cobbles below dams indicated a severe habitat loss below dams. Additional comparison with undisturbed reference streams allowed us to derive management options that could mitigate the negative impact of hydrologic alterations and accumulations of fine sediments downstream of dams. These options are conditional on the season and in particular address the frequency and duration of low and high flow events.